The Influence of Self Efficacy, Family Environment, and Teachers' Perceptions of Welfare on the Interest to Become an Accounting Teacher - Whan Azizah Afifa; Margunani Margunani (Universitas Negeri Semarang, 2023)
The purpose of this study was to examine the effect of self-efficacy, family environment and perceptions of teacher welfare on interest in becoming an accounting teacher in 2019 FE UNNES accounting education students. This research is a population study, namely the 2019 FE UNNES accounting education students totaling 115 students where all respondents were used as the unit of analysis. The data analysis technique used descriptive statistical analysis and multiple linear regression analysis. The results showed that self-efficacy, family environment, and perceptions of teacher welfare had a positive and significant effect on interest in becoming an accounting teacher. Self efficacy, family environment and perceptions of teacher welfare partially have a positive and significant effect on interest in becoming an accounting teacher. Suggestions given by researchers to maintain student interest in becoming teachers are to pay more attention, such as seeking information related to the latest regulations of the teaching profession from various reference sources, attending educational seminars related to learning innovations and adding insight related to the rights of teachers' obligations such as certification. teachers, teacher compensation, and teacher welfare guarantees so as to increase interest in becoming a teacher in educational students.